Indispensable when leaders really matter - Mukunda, Gautam (Boston Harvard Business Review Press, 2012)
In Indispensable, Harvard Business School professor Gautam Mukunda offers an enticingly fresh look at how and when individual leaders really can make a difference. By identifying and analyzing the hidden patterns of their careers, and by exploring the systems that place these leaders in positions of power, Indispensable sheds new light on how we may be able to identify the best leaders and what lessons we can learn, from both the process and the result.
Includes bibliographical references (p. 275-289) and index.
Keywords: Leadership